Modulation of Pacific Sea Surface Temperatures on the Late-Season Tropical Cyclone Tracks Over the Western North Pacific and its Implication for Seasonal Forecasting - Yu, Hua; Wang, Chao; Ge, Xuyang (Frontiers in Earth Science, 2022)
In this study, two leading modes of the late season (October-December) TC track frequency are identified with the empirical orthogonal function analysis. It is found that circulation anomalies associated with the two modes are linked to the concurrent El Niño-Southern Oscillation (ENSO), but with distinct locations of sea surface temperature (SST) maximum. For the first mode, the maximum SST warming and the resulted heating can extend to the equatorial central Pacific, which emanates a cyclonic circulation extending to the east of the Philippines, and then generates an anti-cyclonic circulation to the west of the Philippines by dry advection and local air sea interaction. In contrast, for the second mode, the maximum SST warming and the corresponding heating shift eastward to the equatorial eastern Pacific, the related cyclonic circulation and the compensation descending motion migrate eastward and be confined to the east of 150°E. The associated suppressed heating then emanates an anti-cyclonic circulation to the west of 150°E. These anomalous circulations can modulate TC genesis and steering flow and thus contribute to variations in the two modes. A set of physics-based empirical models is further built, which shows a promising pathway for the seasonal forecasting of the two modes and the basin-wide total TC track frequency. The results highlight the importance of the location of ENSO maximum SST in understanding and seasonal predicting of the late season TC tracks over the WNP.